Correlation Records of VLF Hiss and Ionospheric Absorption of Cosmic Radio Noises at Syowa Station, Antarctica in 1972 - イソザキ, ススム; オセ, マサミ; オンドウ, タダノリ; ISOZAKI, Susumu; OSE, Masami; ONDOH, Tadanori (National Institute of Polar Research, 1974)
P(論文) departmental bulletin paper